Kinetically resolved states of the Halobacterium halobium flagellar motor switch and modulation of the switch by sensory rhodopsin I. - McCain, D A (1987)
Spontaneous switching of the rotation sense of the flagellar motor of the archaebacterium Halobacterium halobium and modulation of the switch by attractant and repellent photostimuli were analyzed by using a computerized cell-tracking system with 67-ms resolution coupled to electronic shutters. The data fit a three-state model of the switch, in which a Poisson process governs the transition from state N (nonreversing) to state R (reversing). After a reversal, the switch returns to state N, passing through an intermediate state I (inactive), which produces a ca. 2-s period of low reversal frequency before the state N Poisson rate is restored. The stochastic nature of the H. halobium switch reveals a close similarity to Escherichia coli flagellar motor properties as elucidated previously. Sensory modulation of the switch by both photoattractant and photorepellent signals can be interpreted in terms of modulation of the single forward rate constant of the N to R transition. Insight into the mechanism of modulation by the phototaxis receptor sensory rhodopsin I (SR-I) was gained by increasing the lifetime of the principal photointermediate of the SR-I photochemical reaction cycle, S373, by replacing the native chromophore, all-trans-retinal, with the acyclic analog, 3,7,11-trimethyl-2,4,6,8-dodecapentaenal. Flash photolysis of analog-containing cells revealed an eightfold decrease in the rate of thermal decay of S373, and behavioral analysis showed longer periods of reversal suppression than that of cells with the native chromophore over similar ranges of illumination intensities. This indicates that attractant signaling is governed by the lifetime of the S373 intermediate rather than by the frequency of photocycling. In this sense, SR-I is similar to rhodopsin, whose function depends on an active photoproduct (Meta-II).